Ant sampling: the importance of pitfall trap depth as a bias factor. Issue 9 (11th September 2020) - Jiménez‐Carmona, Francisco; Carpintero, Soledad; Reyes‐López, Joaquín Luís
Abstract: When sampling with pitfall traps, possible bias factors should be considered. In this study we compare traps of two depths. The results show that, on average, deeper traps captured more ant species (Hymenoptera: Formicidae) and higher numbers of workers, and that the relative abundances of the species were different depending on the depth of the trap, regardless of the type of habitat. Abstract : When sampling with pitfall traps, possible bias factors should be considered. In this study we compare traps of two depths. The results show that, on average, deeper traps captured more ant species (Hymenoptera: Formicidae) and higher numbers of workers, and that the relative abundances of the species were different depending on the depth of the trap, regardless of the type of habitat.